Unusual Route of Impaction, Hypopharyngeal non Penetrating Steel Shrapnel Foreign Body - Ahmed Al-Juboori; Abdalla Mirghani; Amira Nasser Al Hail (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2017)
Foreign body injury is one of the most commonly encountered otorhinolaryngologic emergencies. The diagnosis and management of foreign bodies have mainly been based on the type and location of the foreign body. The workplace is a significant contributor to fatal and non-fatal injuries worldwide and an insufficiently appreciated contributor to the total burden of health care costs. Steel workers sustain a higher occupational hazard of penetrating injuries anywhere in the body, including the head and neck. However, we found no reports in the literature about non-penetrating shrapnel foreign body injuries, particularly in the upper aero-digestive tract. This is a case report of a twenty-five years old steelworker who presented to the emergency department in Al Wakra Hospital with a history of non-penetrating steel foreign body impaction in the throat which had been visualized by Glide Scope and removed successfully with the assistance of Macintosh laryngoscope without complications. The purpose of this presentation is to highlight the unusual route taken by a shrapnel non-penetrating foreign body, through the open mouth to the hypo pharynx. Also, probably this could be the first such case to be reported. A note has, also, been added about its visualization and method of removal, comparing two different techniques.